Abrasive wear of nanostructured cermet coatings in dry and slurry conditions. (November 2021) - Basak, A.K.; Celis, J.-P.; Vardavoulias, M.; Matteazzi, P.
Abstract: Abrasive wear behaviour of WC-Co and Fe/Cu-based nanostructured coatings has been investigated under dry and slurry conditions in this study. The retention of nanostructured coating constituents was confirmed together with the formation of various metallic and ceramic phases. Abrasive wear rate of nanostructured WC-Co coating was one order lower than that of micro-structured coatings in both conditions. Relatively higher abrasion wear resistance of such coatings compare to reference metallic material was because of comparatively smaller debris formation. These debris roll in between the moving surfaces and thus limit the wear of coating materials. Another aspect of higher abrasive wear resistance is homogeneous distribution of hard (WC and Al2 O3 ) particles within relatively soft matrix (Co and FeCu) as revealed by SEM investigation. Highlights: Nanostructured coatings were successfully deposited from engineered nanosized powders using high thermal spraying. Abrasive wear rate of nanostructured WC-based coating is one order of magnitude lower than that of micro-structured coating. Different coating groups (WC-based or Fe/Cu-based) show different degradation mechanism during abrasion.